Peroxisome Proliferator-Activated Receptor-γ in Thyroid Autoimmunity - Silvia Martina Ferrari; Poupak Fallahi; Roberto Vita; Alessandro Antonelli; Salvatore Benvenga (PPAR Research)
Peroxisome proliferator-activated receptor- (PPAR-) γ expression has been shown in thyroid tissue from patients with thyroiditis or Graves’ disease and furthermore in the orbital tissue of patients with Graves’ ophthalmopathy (GO), such as in extraocular muscle cells. An increasing body of evidence shows the importance of the (C-X-C motif) receptor 3 (CXCR3) and cognate chemokines (C-X-C motif) ligand (CXCL)9, CXCL10, and CXCL11, in the T helper 1 immune response and in inflammatory diseases such as thyroid autoimmune disorders. PPAR-γ agonists show a strong inhibitory effect on the expression and release of CXCR3 chemokines, in vitro, in various kinds of cells, such as thyrocytes, and in orbital fibroblasts, preadipocytes, and myoblasts from patients with GO. Recently, it has been demonstrated that rosiglitazone is involved in a higher risk of heart failure, stroke, and all-cause mortality in old patients. On the contrary, pioglitazone has not shown these effects until now; this favors pioglitazone for a possible use in patients with thyroid autoimmunity. However, further studies are ongoing to explore the use of new PPAR-γ agonists in the treatment of thyroid autoimmune disorders.